Embryonic esophageal rhabdomyosarcoma in an adult male: A case report and literature review - Xiaoman Zhang; Guang Li (Frontiers in Oncology, 2022)
Basic principleThere exists a rare aggressive neoplasm called esophageal rhabdomyosarcoma. It originates in cells of the striated muscle or mesenchymal cells which differ from the striated muscle. This tumor has a high degree of malignancy and extensive metastasis. Masses of the sick people are at a high phase when going to hospital. Consequently, the prognosis is exceedingly bad.Patient concernsA 54-year-old male presented with dysphagia as the initial symptom. Gastroscopy showed an irregular protuberant lesion about 18–22 cm from the incisor. The lesion was observed to be pathological under gastroscopy and was diagnosed as an (esophageal) sarcoma.DiagnosisEmbryonic esophageal rhabdomyosarcoma.InterventionsAfter receiving two cycles of DP (docetaxel and cisplatin) chemotherapy in the local hospital, the patient received 60 Gy of radiotherapy in 30 fractions combined with chemotherapy at our hospital. Dysphagia was relieved, and the tumor appeared significantly shrunken on imaging after the treatment.OutcomesLung metastasis occurred 1 month after radiotherapy, and the patient died of pulmonary edema on March 11, 2022.LessonsPreviously reported cases of embryonic esophageal rhabdomyosarcoma are few. Theoretically, the disease should occur in adolescents; nevertheless, our case was a man who was in middle-aged; the neoplasm was in an unusual position: the upper part of the esophagus. Moreover, the patient initially had good response to the combination of radiotherapy and chemotherapy. Although he died 8 months after diagnosis, the presented data represent a valuable resource for understanding the survival benefits of treating embryonic esophageal rhabdomyosarcoma patients with radiotherapy combined with chemotherapy. In addition, we reviewed the previously reported literature, and a total of 17 cases of esophageal rhabdomyosarcoma were identified and analyzed.